Tradisi Sedekah Bumi Sebagai Sarana Membangun Moderasi Beragama di Kampung Moderasi Beragama Desa Bangun Rejo Kecamatan Sukakarya - Tri Mardiana; Purwandari, Elce; Purna Irawan; Depi Putri; Artiyanto (AL-MUTSLA, 2025)
This study aims to examine the role of the Sedekah Bumi (Earth Alms) tradition in fostering religious moderation in the Religious Moderation Village of Bangun Rejo, Sukakarya Subdistrict. The research employs a qualitative method with data collected through in-depth interviews, participatory observation, and documentation. Informants include traditional leaders, religious figures, village officials, youth representatives, teachers, and local residents. The findings reveal that Sedekah Bumi serves as an effective platform for interfaith social interaction, promoting values of tolerance, mutual respect, and communal harmony. Key supporting factors include strong support from village authorities, active interfaith involvement, the participation of youth and women, and a shared commitment to cultural preservation. The main challenges arise from globalization and the lack of regeneration among cultural leaders. Ultimately, the Sedekah Bumi tradition not only strengthens social cohesion but also represents a local strategy for sustaining peace and unity within a diverse society.